Investigating the Potential Quality Markers of Danxi Granule against Ischemic Stroke Using an Absorbed into Blood-Fingerprint-Network-Verification Approach - Wan, Shun; Sun, Yu; Yang, Zhi-wei; Tao, Xin-ru; Cai, Yuan; Li, Peng-hui; Peng, Yan-mei; Wang, Wei (Current Traditional Medicine, 2026)
BackgroundCerebral ischemic stroke (CIS) severely endangers health, and there is an urgent need for effective therapeutic drugs and in-depth research on its mechanism of action. Danxi Granule has potential application in the relevant treatment.ObjectiveThis study aimed to explore the potential quality markers, therapeutic targets, and molecular mechanisms of Danxi Granule in treating CIS through the “Absorbed into Blood- Fingerprint-Network-Verification” paradigm.MethodsAn MCAO rat model was established. Serum samples from three groups were analyzed by UPLC-MS to identify blood-absorbed prototype components. The fingerprint and measurable chemical components of Danxi Granule were obtained using specific chromatographic conditions. Potential quality markers were determined by cross-referencing. Network pharmacology, with databases like GeneCards and OMIM, and relevant software, were used for gene identification and pathway enrichment analysis. Five identified compounds were tested in an OGD/R-induced HT22 cell model.ResultsA total of 207 blood-absorbed prototype components were identified. Ten-batch fingerprint analysis of Danxi Granules showed high similarity, with 15 common peaks (8 corresponding to measurable constituents). Five potential quality markers were determined. These compounds targeted 184 genes, intersecting with 73 disease-related ones. Network analysis revealed 10 key genes and cellular experiments confirmed the protection of HT22 cells, with TNF as a core target.DiscussionIn this study, an HPLC fingerprint was established using UPLC-MS technology, and five potential Q-markers were screened out. Through network pharmacology and cell experiments, these markers were validated to exert anti-CIS effects via mechanisms, such as anti-inflammation, thereby revealing the material basis of the pharmacological effects of Danxi Granules. The findings of this study provide a basis and new perspectives for quality standard research, clinical application, and the modernization of complex traditional Chinese medicine (TCM) systems. However, the current mechanistic investigation remains at a superficial level, and subsequent studies should further deepen the systematic exploration of the underlying action mechanisms.ConclusionThe “absorbed into blood-fingerprint” paradigm identified five potential quality markers, namely cryptotanshinone, tanshinone IIA, aurantio-obtusin, icariin, and paeoniflorin. Validation through the “network-verification” paradigm confirmed their quality marker status and demonstrated that their anti-CIS mechanisms likely involve suppressing TNF-α, IL-6, and IL-1β expressions, thereby exerting anti-inflammatory effects.
Keywords: network pharmacology